The treatment of recurrent depression in Iceland: A comparison of the application of antidepressant medication and cognitive behavior therapy - Anna Guðmundsdóttir 1993- (2020)
Depressive disorders are the most common mental disorders, affecting 300 million people worldwide. A large number of depressed people do not seek professional help despite a variety of effective evidence-based treatments for depression, most common being antidepressant medication (ADM) and cognitive behavior therapy (CBT). Service use and treatment quality have scarcely been researched in Iceland. The primary objective of this study was to get a description of routine therapy for depression that people with recurrent depression in Iceland receive. Participants in this study consisted of 101 individuals with a history of recurrent depression and 54 never depressed individuals, from the general population. The treatment history of the formerly depressed participants was assessed with a semi-structured interview, focusing on ADM and CBT. A vast majority had a history of current or former ADM and half had a history of CBT. Around half of all CBTs were shorten than eight sessions. Both individual and group CBT delivered key components of the therapy well on average. The advantage of individual CBT is case-conceptualization and group CBT is better at dilivering structure and reading material. Attitude measurements showed a clear preference for psychotherapy with all participants. These results show that pharmacotherapy is dominant in treating recurrent depression in Iceland and improvements in the therapeutic environment are needed to offer CBT as a cost-effective option in psychotherapy in Iceland. Þunglyndi er algengasta geðröskunin og hefur áhrif á líf 300 milljón manna á hverri stundu. Stór hluti þeirra sem þjást af þunglyndi leita sér ekki sérfræði- aðstoðar þrátt fyrir framboð á gagnreyndum meðferðum við þunglyndi. Alengustu meðferðirnar eru þunglyndislyfjameðferð og hugræn atferlismeðferð (HAM). Notkun og gæði heilbrigðisþjónustu hafa lítið verið rannsökuð á Íslandi. Markmið þessarar rannsóknar er að fá yfirlit yfir þá vanabundnu meðferð sem fólk með endurtekið þunglyndi hefur fengið. Þátttakendur í ...